Research Progress on X-site Doping of All-inorganic Perovskite CsPbX3 Nanocrystals - Xiang, Xuanrui; Guan, Hanyue; Zhao, Liting; Lu, Huiping (International Journal of Materials Science and Technology Studies, 2025)
All-inorganic perovskite CsPbX3 (X=Cl, Br, I) nanocrystals have attracted extensive attention due to their excellent photoelectric properties. These materials not only have the advantages of tunable emission wavelength, emission peak width and high fluorescence quantum yield, but also are significantly superior to traditional organic-inorganic hybrid systems in terms of device compatibility and environmental stability. They have shown great application potential in the field of optoelectronic devices and have been successfully applied to the construction of functional modules such as light-emitting layer (LEDs), photovoltaic light-absorbing layers and laser gain medium. In recent years, it has become a research hotspot to regulate the physical and chemical properties of CsPbX3 nanocrystals through ion doping engineering. The doping strategy can effectively adjust the band structure and luminescence properties of the material, and its mechanism is mainly due to the perturbation of the crystal field and the modification of the defect state by the doping elements. In this paper, the international research trends of X-site doping of this material are systematically reviewed. The crystal structure characteristics, optical performance regulation mechanism and mainstream preparation technology are described. The optimization mechanism of halogen site chemical modification on the photoelectric properties of materials is analyzed. Finally, the current technical bottleneck and future development direction are discussed.